The Effect of Expectations Disconfirmation and Employee Expertise on Revisit Intention and Recommendation through Tourists’ Satisfaction: EDT Lens - Yuwono, Daniel; Syofyan, Syofriza; Aseanty, Deasy; Usman, Bahtiar (University of Merdeka Malang, 2024)
This study aims to analyse the effect of customer expectations (disconfirmation) and employee expertise on revisit interest and the tendency to recommend through customer satisfaction as an intervening variable. This study uses a quantitative research design with an explanatory research approach. Data were collected through questionnaires distributed to tourists. Data analysis using Structural Equation Modeling (SEM) with WarpPLS.The results showed that: Customer expectation (disconfirmation) and employee expertise have a positive effect on customer satisfaction. As well as customer satisfaction has a positive effect on return visit interest and the tendency to recommend. This study make a significant contribution to the understanding of the relationship between customer expectations (disconfirmation), employee expertise, customer satisfaction, return visit interest, and propensity to recommend. The results of this study can also help the tourism industry to develop appropriate strategies and programmes to improve customer expectations (disconfirmation), employee expertise, and customer satisfaction.